2010
DOI: 10.1177/1741143210373741
|View full text |Cite
|
Sign up to set email alerts
|

South African Female Principals’ Career Paths: Understanding the Gender Gap in Secondary School Management

Abstract: This article reports on data from a larger scale study exploring female principals' experiences of their career route to the principalship of secondary schools in South Africa. To understand these experiences, the study used an analytical framework that identifies three phases principals go through on their career route, namely: anticipation, acquisition and performance. The framework suggests that women experience more obstacles than men on their career route and their experiences are influenced by personal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 9 publications
4
96
0
13
Order By: Relevance
“…Similar views were expressed in a study conducted by Moorosi (2010) on South African female Principals' career path who argued that the extent to which equal opportunity policy interventions for advancement of female teachers to principalship were put in place and achieved were not explored. The findings revealed that equal opportunities policy was enshrined in the law but female teachers were not reaping the rewards of equal opportunity enactment.…”
Section: Resultsmentioning
confidence: 69%
“…Similar views were expressed in a study conducted by Moorosi (2010) on South African female Principals' career path who argued that the extent to which equal opportunity policy interventions for advancement of female teachers to principalship were put in place and achieved were not explored. The findings revealed that equal opportunities policy was enshrined in the law but female teachers were not reaping the rewards of equal opportunity enactment.…”
Section: Resultsmentioning
confidence: 69%
“…Since studies have linked promotions with career advancement (Forret & Dougherty, 2001), any factor restricting promotions would be considered as barriers for career advancement. Also, studies have indicated that mostly employees change their jobs for better opportunities (e.g., Ismail & Ibrahim, 2008;Moorosi, 2010). But for many women, apart from career advancement, there could be more reasons why they had to, or could not change their jobs.…”
Section: Factors Affecting Promotion and Job Changementioning
confidence: 99%
“…For example, Moorosi's (2010) McMahon, Limerick, Cranston, and Andersen (2006) tried to document women's reflections on their careers over a ten-year period. They categorized the barriers impacting women's careers as age, familywork balance decisions, personality, gender bias, departmental structure, organizational policy, and geographical location.…”
Section: Barriers To Women For Career Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable examples include Gronn (1999) who proposed a 4 stage career pathway model for head teachers in the UK, namely: formation, accession, incumbency and divestiture; Dimmock and O'Donoghue (1996) who explored the career histories of head teachers in Western Australia; and Rayner and Ribbins (1999) who investigated the professional lives of head teachers in special education in the UK. More recent examples include Moorosi (2010) who studied South African female principals' career paths, Shapira et al (2011) who explored the biographical backgrounds of female school principals in Israel, and Bisschoff and Mackenzie-Batterbury (2013) who explored the life and career journeys of principals leading schools in disadvantaged areas in the UK. While we acknowledge the importance of this body of career journey research, we do not draw on it explicitly in our analysis as the focus of our paper is more on leadership identity rather than the career journey itself.…”
Section: Rq1mentioning
confidence: 99%